2005
DOI: 10.1207/s15402010bsm0301_4
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disturbance and Injury Risk in Young Children

Abstract: The objective of this study was to investigate the relationship between sleep disturbance and both injury rates and injury-prone behaviors in preschool-age and early school-age children, using cross-sectional surveys of sleep disturbance (Children's Sleep Habits Questionnaire) and injury-related behaviors (Injury Behavior Checklist), and chart review of injuries. Participants were 71 patients enrolled in a pediatric clinic in a children's teaching hospital, ages 3 through 7 years, coming either for well-child … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
76
4
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(92 citation statements)
references
References 33 publications
6
76
4
6
Order By: Relevance
“…Previous research has suggested that asthma patients are more likely to experience sleepiness during daytime hours [7,23,24] and that asthma condition and medications for asthma may impair sleep quality [8,25]. Moreover, there is substantial evidence suggesting that daytime sleepiness, inadequate sleep or poor sleep quality is an independent risk factor for injuries in both adults and children [11,12,[26][27][28][29]. Combining the evidence on the three relationships: 1) asthma status and injury; 2) asthma status and its impairment on sleep quality and quantity and 3) inadequacy of sleep and injury, indicates a direct link between asthma status and injury mediated through impaired sleep quality and quantity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has suggested that asthma patients are more likely to experience sleepiness during daytime hours [7,23,24] and that asthma condition and medications for asthma may impair sleep quality [8,25]. Moreover, there is substantial evidence suggesting that daytime sleepiness, inadequate sleep or poor sleep quality is an independent risk factor for injuries in both adults and children [11,12,[26][27][28][29]. Combining the evidence on the three relationships: 1) asthma status and injury; 2) asthma status and its impairment on sleep quality and quantity and 3) inadequacy of sleep and injury, indicates a direct link between asthma status and injury mediated through impaired sleep quality and quantity.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical data suggest that asthma impairs sleep quality and further impairs cognitive performance during the daytime, especially among those with serious night-time symptoms [6][7][8][9][10]. There is a causal relationship between impaired sleep quality and injuries [11,12]. Moreover, it has also been shown that asthma patients are at higher risk of fracture due to reduced bone mass and bruising, [13,14] a known side effect of corticosteroid medication.…”
Section: Introductionmentioning
confidence: 99%
“…19 Bu çalışmada da uykuya yatmadan önce çocukların %39.7'sinin süt içtiği, %4.8'inin yemek yediği belirlendi (Tablo 3 15 tarafından gösterilmiş ve başka bir çalışmada da yatma saati direnci, uykuya dalmada zorluk ve uyku süresinin kısalığının televizyon ile en fazla ilişkili uyku bozuklukları olduğu belirtilmiştir. 36 Bu nedenle TV izlemenin uyku bozuklukları ve çocuk sağlığına olumsuz etkileri konusunda aileler bilgilendirilmeli, uyku hijyeni ve ekoloji ile bağlantısı kurulmalıdır.…”
Section: Tablo 1 çOcukların Ve Ailelerin Bazı Tanımlayıcı öZelliklerunclassified
“…8,11,12 Çocuğun hastalığı, hastalığın akut veya kronik olması, tedavisinin uzun sürmesi gibi durumlarda da çocuğun gelişiminde regresyon görülmekte ve çeşitli davranış problemleri ile birlikte uyku problemleri de görülmektedir. 13,14 Üç-yedi yaş arası çocuklarda yapılan bir çalışmada, şiddetli uyku sorunları olan çocuklarda, yaralanma ve yaralanma eğilimli davranışların daha sık görüldüğü, zor mizaç, hırçınlık ve uyum güçlüklerinin yaşandığı belirlenmiştir 15 Çocuklardaki uyku sorunları, sadece çocuğu değil aileyi de olumsuz etkilemektedir. 5,16,17 Yatağına isteksiz giden ya da gece sürekli olarak uykusundan uyanan çocukların aileleri sıkıntı ve stres yaşamaktadırlar.…”
unclassified
“…
aggressive, deviant behavior; learning capability impairment [3][4][5]. According to international studies, timely diagnostics of sleep disorders and sleep apnea syndrome in outpatient pediatric
…”
mentioning
confidence: 99%